Osmo-convective dehydration kinetics of jackfruit (Artocarpus heterophyllus) - Pragati Kaushal; H.K. Sharma (Journal of the Saudi Society of Agricultural Sciences)
Osmotic dehydration is a process in which partial water is removed by immersion of water containing cellular solid in a concentrated aqueous solution of high osmotic media for a specific time and temperature. Preliminary trials were planned for finalizing the concentration of osmolyte (salt solution: 5%, 10%, 15% and 20%). The osmotically pre-treated samples were dried at 50 °C which were examined using sensory parameters. On the basis of sensory parameters, 15% salt solution concentration was considered best. The osmotically pre-treated jackfruit samples of 15% salt solution were convectively dehydrated in a tray dryer at air temperatures of 50, 60 and 70 °C at constant velocity of 1.5 m/s air flow in perforated trays. Results indicated that drying took place in falling rate period. The sample dried at 60 °C was found better in color as compared to samples at 50 and 70 °C. Mathematical models were fitted to the experimental data and the performance of these models was evaluated by comparing the coefficient of determination (R2), Root mean square error (RMSE), reduced chi-square (χ2), percent mean relative deviation modulus (E%) between observed and predicted moisture ratio. The best model was chosen as one with the highest coefficient of correlation (R2); and the least χ2, RMSE and mean relative deviation modulus (E). Wang and Singh model, having χ2 and RMSE value (at 60 °C) of 0.00027 and 0.01655 respectively gave the best results for describing the drying behavior of jackfruit samples.